PLANETARY TEMPERATURES IN THE PRESENCE OF AN INERT, NONRADIATIVE ATMOSPHERE - Nicol, John Leslie (Quaestiones Geographicae, 2020)
This study considers solid planets at about 300 K and an inert atmosphere having no interaction with associated radiation. Processes considered include transfer of energy from the surface skin to underlying layers depending on thermal properties. Temperatures of the surface depend on the rates of transfer of energy between soil layers. The atmosphere is warmed at base by contact with the surface, convection and turbulence distributing higher temperatures through the air. Comparisons between theoretical and measured temperatures show a close similarity. Mean planetary temperatures are calculated, depending on thermal parameters and the intensity of light/radiation from the particular solar system.